2020
DOI: 10.1101/2020.07.14.20150979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic epidemiology of the early stages of SARS-CoV-2 outbreak in Russia

Abstract: The ongoing pandemic of SARS-CoV-2 presents novel challenges and opportunities for the use of phylogenetics to understand and control its spread. Here, we analyze the emergence of SARS-CoV-2 in Russia in March and April 2020. Combining phylogeographic analysis with travel history data, we estimate that the sampled viral diversity has originated from 67 closely timed introductions into Russia, mostly in late February to early March. All but one of these introductions came from non-Chinese sources, suggesting th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…This is backed up by the presence of Moscow-derived samples appearing at a large portion of larger cluster junctions in our diagram, indicating travel that may have led to outbreaks in other cities such as Omsk and Saint Petersburg. Additionally, Komissarov et al [38] have identified nine distinct transmission networks within the Russian Federation, making use of similar data obtained from GISAID [38]. Several of the transmission networks deduced by Komissarov et al include transmissions from Moscow to Yakutia, from Krasnodar to Orenburg, and from Moscow to Sverdlovsk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is backed up by the presence of Moscow-derived samples appearing at a large portion of larger cluster junctions in our diagram, indicating travel that may have led to outbreaks in other cities such as Omsk and Saint Petersburg. Additionally, Komissarov et al [38] have identified nine distinct transmission networks within the Russian Federation, making use of similar data obtained from GISAID [38]. Several of the transmission networks deduced by Komissarov et al include transmissions from Moscow to Yakutia, from Krasnodar to Orenburg, and from Moscow to Sverdlovsk.…”
Section: Resultsmentioning
confidence: 99%
“…3) also shares several similarities with the literature, despite the difficulty in making more concrete comparisons due to the lack of extensive epidemiological data. Kozlovskaya et al [37] state that the first several cases identified in Russia for the latter transmission pathway [38]. Additionally, several large outbreaks are seen in Saint Petersburg, since similar data has been used, these outbreaks may contribute to outbreaks at the Vreden Hospital which occurred somewhere from late-March to early-April [38].…”
Section: Spread Of Covid19 In Russiamentioning
confidence: 99%
“…The Russian epidemic was characterized by influx from other countries. 19 In areas where crude oil exports are active, the virus may spread due to inflows from other countries even in remote areas with a small population.…”
Section: Russiamentioning
confidence: 99%
“…Moreover, it is unclear how industrial structure and affluence affect infection trends in countries with large regional economic disparities, such as Russia. It also remains enigmatic whether policy is the only factor behind the success of countries resilient to coronavirus disease 2019 (COVID- 19), such as New Zealand 10 and Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…In the ongoing pandemic, large scale whole genome sequencing initiatives in other countries are being used to establish the origins of the spreading infections as well as to determine how the virus has mutated during its transmission (9). Viral genome sequencing and epidemiological data have also been successfully used to estimate the impact of informed public health decisions on the spread of the virus and contact tracing of cluster cases (10). Hence, large scale generation of whole-genome sequence data on SARS-CoV-2 from clinical samples collected from multiple geographic locations and at different time points of the outbreak and rapid dissemination of the same in public databases like the Global Initiative on Sharing All Influenza Data (GISAID) (11), is expected to provide valuable information.…”
Section: Introductionmentioning
confidence: 99%